Role of Social Capital In Shaping Partnerships Within Interorganizational Networks - Maja JOKIEL1; Grzegorz JOKIEL1; Agnieszka MLODZINSKA-GRANEK2 (Communications of International Proceedings, 2021)
The goal of the research introduced in the article is the identification of the role social capital plays in the process of partnership creation within interorganizational networks. In some societies social capital is at its very low levels. There are many studies explaining the reasons behind it, focusing mainly on formal/measurable factors. There are not many publications that overlook the institutional aspects of partnerships, and focus rather on its relational context. This article is about the process of shaping relational partnership and the role social capital plays in this process, in the context of interorganizational networks. The Authors claim that high level of social capital has a positive impact on shaping partherships in such networks. In order to prove that thesis, the Authors conducted empirical research, which results are introduced in this article. The article consist of three parts: (1) definition of the idea of partnership in the context of interorganizational networks; (2) definitions and concepts of social capital; (3) research results on the role social capital plays in shaping partnerships within interorganizational networks. The article is based on empirical research – it containts results of research conducted in October and November 2020, among sixty respondents, from 19 clusters in Poland. The research tool was CATI, the statistical analysis has been run by the Authors of this article with Excel tool. The results of the research showed that: (1) respondents understand partnership rather as relation with other organizations in a cluster than any kind of institutionalized form of cooperation; (2) the relational factors (such as: knowledge sharing, cooperation with engaged people,  readiness to provide support and exchange of informal information) are more important to respondents than profit factors; (3) coordinators (leaders) are crucial for partnerships to work; (4) organizations become more aware of the benefits of cooperation; (5) in situation of unsuccessful projects, partners are first trying to minimize their individual financial losses.
Keywords: Partnership; Social capital; Interorganizational network